Accelerating & Optimizing: Making Organization Website Using React.js & Node.js - Maulana, Fikri Naufal; Pebriano Nurba, Putra; Rizky, Muhammad; Hendra, Hendra; Adharani, Yana; Rosanty, Nurvelly; Nurbaya Ambo, Sitti (Society : Jurnal Pengabdian Masyarakat, 2025)
In the digital transformation era, many local and student organizations still face issues related to the lack of professional websites, low digital visibility, and limited IT personnel. This community service project aimed to support these organizations by accelerating and optimizing the development of organizational websites using React.js for front-end interface creation and Node.js as the server-side runtime. Through a series of workshops and technical mentoring conducted during the KKN program at Universitas Muhammadiyah Jakarta, the team implemented a step-by-step approach: from system requirement analysis, project initialization using React CLI, component-based user interface development, integration with Tailwind CSS for styling, to deployment via GitHub Pages. The program enabled participants to directly practice developing responsive, maintainable, and scalable websites that reflect modern web standards. The outcomes show that React.js significantly increases development speed and modularity, while Tailwind CSS enhances visual consistency and ease of use. Community partners gained new skills and were able to independently manage and expand their organizational websites post-program. This activity contributes to improving the digital competency of grassroots organizations and promoting technology adoption for sustainability.